ULTRA PETITUM PARTIUM DALAM PERKARA PERCERAIAN MENURUT HUKUM ACARA PERADILAN AGAMA DAN YURISPRUDENSI MAHKAMAH AGUNG - Fadhilah (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2019)
Abstract Review of the Ultra Petitum Partium Principle according to the Law of the Religious Court and Jurisprudence of the Supreme Court and also the application of Utra Petitum Partium in divorce case No. Case 254 / Pdt.G / 2014 / MS-Ksg. To get answers from these studies the author uses normative juridical research methods that are qualitative with a descriptive analytical approach that is by collecting, compiling, clarifying and analyzing data to solve problems systematically and accurately. The results of the research show that the Ultra Petitum Partium Principle according to the Religious Court Procedural Law, namely Article 178 paragraph 1HIR does not apply absolutely because the Judges in carrying out their duties must act actively and provide decisions that actually resolve the case as long as the decision is in accordance with the core Petitum Primair, whereas according to the Supreme Court Jurisprudence Principle, it is justified for judges to drop Ultra Petitum as long as it is still in accordance with the material events permitted or in accordance with posita, as contained in MARI's decision No. 556K / Sip / 1971 and MARI No. 425.K / Sip / 1975: 3. The application of Ulum Petitum Partium in divorce case No. Case 254 / Pdt.G / 2014 / MS-Ksg in the Kuala Simpang Court, which is to consider that the legal event experienced by the plaintiff is what Article 19 letter (f) Government Regulation Number reads. 9 of 1975 in conjunction with Article 116 letter (f) Compilation of Islamic Law because the plaintiff requested a verdict that was as fair as possible to be granted to take the duration of the defendant to leave the plaintiff for 8 months, therefore the Judge said the Ultra Petitum Partium in the case rested on the Jurisprudence which reads , the judex facti decision based on Petitum Subsidai in the form of ex quo et bono, because in order to grant the plaintiff's subsidies, according to the panel of judges, it did not violate the Ultra Petitum Partium Principle and was in line with the jurispudence. Keywords: Ultra Petitum Partium according to the Religious Court Procedure Law and the Supreme Court Jurisprudence. Abstrak Tinjauan tentang Asas Ultra Petitum Partium menurut Hukum Acara Peradilan Agama dan Yurisprudensi Mahkamah Agung dan juga penerapan Utra Petitum Partium dalam perkara perceraian No. Perkara 254/Pdt.G/2014/MS-Ksg. Untuk mendapatkan jawaban dari penelitian tersebut penulis menggunakan metode penelitian yuridis normatif yang bersifat kualitatif dengan pendekatan deskriptif analitis yaitu dengan cara mengumpulkan, menyusun, mengklarifikasi dan menganalisa data untuk memecahkan permasalahan yang secara sistematis dan akurat. Dari hasil penelitian menunjukkan bahwa Asas Ultra Petitum Partium menurut Hukum Acara Peradilan Agama yaitu Pasal 178 ayat 1HIR tidak berlaku secara mutlak sebab Hakim dalam menjalankan tugasnya harus bertindak secara aktif dan memberikan putusan yang benar-benar menyelesaikan perkara selama putusan tersebut sesuai denga inti Petitum Primair, sedangkan menurut Asas Yurisprudensi Mahkamah Agung dibenarkan bagi hakim menjatuhkan Ultra Petitum asalkan masih sesuai dengan kejadian materil yang di izinkan atau sesuai posita, sebagaimana terdapat dalam putusan MARI No. 556K/Sip/1971 dan MARI No. 425.K/Sip/1975:3. Adapun penerapan Ultar Petitum Partium dalam perkara perceraian No. Perkara 254/Pdt.G/2014/MS-Ksg di Mahkamah Kuala Simpang yaitu menimbang bahwa peristiwa hukum yang di alami penggugat tersebut adalah sebagai mana bunyi Pasal 19 huruf (f) Peraturan Pemerintah Nomor. 9 Tahun 1975 jo Pasal 116 huruf (f) Kompilasi Hukum Islam karna penggugat meminta putusan yang seadil-adilnya sangat layak untuk dikabulkan mengigat lamanya tergugat meninggalkan penggugat selama 8 bulan, maka dari itu Hakim meneratkan Ultra Petitum Partium dalam perkara tersebut bersandar pada Yurisprudensi yang berbunyi, putusan judex facti yang didasarkan pada Petitum Subsidai yang berbentuk ex quo et bono, karena untuk mengabulkan subsidai penggugat tersebut menurut majelis Hakim tidak melanggar Asas Ultra Petitum Partium Dan telah sejalan dengan Yurispudensi tersebut. Kata Kunci: Ultra Petitum Partium menurut Hukum Acara Peradilan Agama dan Yurisprudensi Mahkamah Agung.